The Role of Hospital By Laws in Providing Legal Protection Against Alleged Medical Malpractice at the Padang Panjang City Regional General Hospital - Yofiza Media; Maiyestati; Prima Resi Putri (Yayasan Multidimensi Kreatif, 2024)
Hospital By Laws (HBL) is an internal hospital rule designed to provide legal protection to both patients and medical personnel. In the context of Padang Panjang Hospital, HBL should function as a reference in resolving medical disputes and maintaining the quality of health services. Based on the analysis of the situation, HBL has not functioned optimally, especially in dealing with cases of alleged medical malpractice. The purpose of this study was to analyze the role of HBL in providing legal protection against alleged medical malpractice at Padang Panjang Hospital, as well as to find obstacles faced in its implementation. The method used is a sociological juridical approach with primary data obtained through interviews with related parties in the hospital, and secondary data from related legal literature. The results of the study show that many cases of alleged malpractice are resolved informally through mediation, without using strict legal procedures based on HBL. Several cases such as misalignment of surgery, incorrect installation of infusions in infants, and negligence in the installation of Nasogastric Tube (NGT) are examples of the weak implementation of HBL at Padang Panjang Hospital. The main obstacle found in the implementation of HBL is the lack of understanding and awareness from hospitals of the importance of HBL as a legal instrument. Dispute resolution is more often carried out through a family approach without involving the formal rules regulated in the HBL. This shows that there is a gap between existing regulations and practices carried out in the field. The supervision mechanism for the implementation of HBL in hospitals has also not run well, so this rule is not functioning as it should. This study suggests the need to strengthen the implementation of HBL at Padang Panjang Hospital through more intensive socialization to all medical personnel and hospital management as well as training on professional ethics and medical service standards. Supervision is needed to ensure that these rules are properly implemented in resolving medical disputes. Padang Panjang Hospital is expected to improve the quality of its services while providing better legal protection for patients.